1991
DOI: 10.1080/03670244.1991.9991163
|View full text |Cite
|
Sign up to set email alerts
|

Household economic strategies and food expenditure patterns in rural Mexico: Impact on nutritional status of preschool children

Abstract: This paper examines the nutritional impact of 1) household economic strategies (source of income, women's contribution to income, and subsistence production) and 2) resource allocation patterns. In a survey of 178 rural Mexican households, the following were recorded during winter and summer: 1) income by source and earner; 2) gifts and loans; 3) agricultural production and expenses; 4) household food use; 5) non-food purchases; 6) household composition; and 7) anthropometric indices and morbidity of preschool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
2

Year Published

1991
1991
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 24 publications
3
14
2
Order By: Relevance
“…Few studies have distinguished source of income from type of income, but Kaiser and Dewey (1991) found that sporadic remittances were associated with decreased food quality and with retarded growth of preschool children in rural Mexico. Lump sums tend to be spent on consumer durables, such as roofing sheets or bicycles, which require significant savings to buy and may be the ''target'' for which migration was undertaken.…”
Section: Migrant Remittancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have distinguished source of income from type of income, but Kaiser and Dewey (1991) found that sporadic remittances were associated with decreased food quality and with retarded growth of preschool children in rural Mexico. Lump sums tend to be spent on consumer durables, such as roofing sheets or bicycles, which require significant savings to buy and may be the ''target'' for which migration was undertaken.…”
Section: Migrant Remittancesmentioning
confidence: 99%
“…10. They lead to irregular intakes because of irregular income (Fleuret and Fleuret 1980;Kaiser and Dewey 1991;Trenchard 1987;von Braun et al 1994). 11.…”
Section: Within-rural Variationmentioning
confidence: 99%
“…This includes control of cash income, which as Kaiser and Dewey (1991) contend, husbands are less likely to use for the welfare of wives and children due to their different expenditure patterns. Our results in this respect also accord with those of Fortmann (1982) for Tanzania.…”
Section: Concluding Commentsmentioning
confidence: 99%
“…Commercialisation may affect differently the welfare of various members, depending on how work and responsibilities and control over income within a household change (von Braun, de Haen and Blanken, 1991;Kaiser and Dewey, 1991;Julin, 1993;Angelique, 1995).…”
Section: Overview Of Relevant Literaturementioning
confidence: 99%
See 1 more Smart Citation